Deoxydehydration of 1, 4-anhydroerythritol over anatase TiO2(101)-supported ReOx and MoOx. Issue 11 (20th May 2020) - Xi, Yongjie; Lauterbach, Jochen; Pagan-Torres, Yomaira; Heyden, Andreas
Abstract : Heterogeneously catalyzed deoxydehydration (DODH) ordinarily occurs over oxide supported ReO x sites. A comparably high activity of MoO x /TiO2 (101) suggests that it is a promising low-cost DODH catalyst that can replace Re-based catalysts. Abstract : Heterogeneously catalyzed deoxydehydration (DODH) ordinarily occurs over relatively costly oxide supported ReO x sites and is an effective process for the removal of vicinal OH groups that are common in biomass-derived chemicals. Here, through first-principles calculations, we investigate the DODH of 1, 4-anhydroerythritol over anatase TiO2 (101)-supported ReO x and MoO x . The atomistic structures of ReO x and MoO x under typical reaction conditions were identified with constrained thermodynamics calculations as ReO2 (2O)/6H–TiO2 and MoO(2O)/3H–TiO2, respectively. The calculated energy profile and developed microkinetic reaction model suggest that both ReO2 (2O)/6H–TiO2 and MoO(2O)/3H–TiO2 exhibit a relatively low DODH activity at 413 K. However, at higher temperatures such as 473 K, MoO(2O)/TiO2 (101) was found to exhibit a reasonably high catalytic activity similar to ReO2 (2O)/6H–TiO2, consistent with a recent experimental study. Mechanistically, the first O–H bond cleavage of 1, 4-anhydroerythritol and the dihydrofuran extrusion were found to be the rate-controlling steps for the reaction over ReO2 (2O)/6H–TiO2 and MoO(2O)/3H–TiO2, respectively. Thus, this study clarifies the mechanism of the DODH over oxide-supported catalysts and provides meaningful insight into the design of low-cost DODH catalysts.